Clinical review of high-flow nasal oxygen therapy in human and veterinary patients - Whitney, Joanna; Keir, Iain (Frontiers in Veterinary Science, 2023)
Oxygen therapy is the first-line treatment for hypoxaemic acute respiratory failure. In veterinary medicine this has traditionally been provided via mask, low-flow nasal oxygen cannulas, oxygen cages and invasive positive pressure ventilation. Traditional non-invasive modalities are limited by the maximum flow rate and fraction of inspired oxygen (FiO2) that can be delivered, variability in oxygen delivery and patient compliance. The invasive techniques are able to provide higher FiO2 in a more predictable manner but are limited by sedation/anaesthesia requirements, potential complications and cost. High-flow nasal oxygen therapy (HFNOT) represents an alternative to conventional oxygen therapy. This modality delivers heated and humidified medical gas at adjustable flow rates, up to 60L/min, and FiO2, up to 100%, via nasal cannulas. It has been proposed that HFNOT improves pulmonary mechanics and reduces respiratory fatigue via reduction of anatomical dead space, provision of low-level positive end-expiratory pressure (PEEP), provision of constant FiO2 at rates corresponding to patient requirements and through improved patient tolerance. Investigations into the use of HFNOT in veterinary patients have increased in frequency since its clinical use was first reported in dogs with acute respiratory failure in 2016. Current indications in dogs include acute respiratory failure associated with pulmonary parenchymal disease, upper airway obstruction and carbon monoxide intoxication. The use of HFNOT has also been advocated in certain conditions in cats and foals. HFNOT is also being used with increasing frequency in the treatment of a widening range of conditions in humans. Although there remains conflict regarding its use and efficacy in some patient groups, overall these reports indicate that HFNOT decreases breathing frequency and work of breathing and reduces the need for escalation of respiratory support. In addition, they provide insight into potential future veterinary applications. Complications of HFNOT have been rarely reported in humans and animals. These are usually self-limiting and typically result in lower morbidity and mortality than those associated with invasive ventilation techniques.